Skin and the Non-Human Human: Transformation and Reversal in Titian's The Flaying of Marsyas - Rosing, Lilian Munk (British journal of psychotherapy, 2013)
The article puts forward an aesthetic and psychoanalytic analysis of Titian's painting, The Flaying of Marsyas, arguing that the painting is a reflection on the human subject as a being constituted by skin and by a core of non‐humanity. The analysis is partly an answer to Melanie Hart's (2007) article ‘Visualizing the mind: Looking at Titian's Flaying of Marsyas', addressing features of the painting not commented on by Hart, and supplementing Hart's (Kleinian) theoretical frame by involving Didier Anzieu's ‘skin ego’, Slavoj Zizek's concept of the ‘non‐human’, Giorgio Agamben's term of the ‘Muselmann’, and Anton Ehrenzweig's psychoanalytic theory of artistic creation. Whereas Hart is focusing on form and colour, I also turn my attention towards the texture of the painting.